Red carotenoids and associated gene expression explain colour variation in frillneck lizards. Issue 1907 (17th July 2019) - McLean, Claire A.; Lutz, Adrian; Rankin, Katrina J.; Elliott, Adam; Moussalli, Adnan; Stuart-Fox, Devi
Abstract : A long-standing hypothesis in evolutionary ecology is that red–orange ornamental colours reliably signal individual quality owing to limited dietary availability of carotenoids and metabolic costs associated with their production, such as the bioconversion of dietary yellow carotenoids to red ketocarotenoids. However, in ectothermic vertebrates, these colours can also be produced by self-synthesized pteridine pigments. As a consequence, the relative ratio of pigment types and their biochemical and genetic basis have implications for the costs and information content of colour signals; yet they remain poorly known in most taxonomic groups. We tested whether red- and yellow-frilled populations of the frillneck lizard, Chlamydosaurus kingii, differ in the ratio of different biochemical classes of carotenoid and pteridine pigments, and examined associated differences in gene expression. We found that, unlike other squamate reptiles, red hues derive from a higher proportion of ketocarotenoids relative to both dietary yellow carotenoids and to pteridines. Whereas red frill skin showed higher expression of several genes associated with carotenoid metabolism, yellow frill skin showed higher expression of genes associated with steroid hormones. Based on the different mechanisms underlying red and yellow signals, we hypothesize that frill colour conveys different information in the two populations. More generally, the data expand our knowledge of the genetic and biochemical basis of colour signals in vertebrates.